2008
DOI: 10.1073/pnas.0711382105
|View full text |Cite
|
Sign up to set email alerts
|

A sonic hedgehog signaling domain in the arterial adventitia supports resident Sca1 + smooth muscle progenitor cells

Abstract: We characterize a sonic hedgehog (Shh) signaling domain restricted to the adventitial layer of artery wall that supports resident Sca1-positive vascular progenitor cells (AdvSca1). Using patched-1 (Ptc1 lacZ ) and patched-2 (Ptc2 lacZ ) reporter mice, adventitial Shh signaling activity was first detected at embryonic day (E) 15.5, reached the highest levels between postnatal day 1 (P1) and P10, was diminished in adult vessels, and colocalized with a circumferential ring of Shh protein deposited between the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
342
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(360 citation statements)
references
References 55 publications
14
342
1
1
Order By: Relevance
“…2H). In agreement with these results, adventitial cells have been shown to respond to Hh signals (28). Because oncogenic Smo expression within pancreatic epithelium was unable to potentiate Kras G12D -mediated neoplasia, we tested whether Hh signaling was active in Kras G12D -driven tumor epithelium by crossing PdxCre;Kras G12D ;SmoM2 mice with the Ptc-LacZ reporter line.…”
Section: Pancreatic Ductal Epithelial Cells Are Incompetent To Transdmentioning
confidence: 59%
“…2H). In agreement with these results, adventitial cells have been shown to respond to Hh signals (28). Because oncogenic Smo expression within pancreatic epithelium was unable to potentiate Kras G12D -mediated neoplasia, we tested whether Hh signaling was active in Kras G12D -driven tumor epithelium by crossing PdxCre;Kras G12D ;SmoM2 mice with the Ptc-LacZ reporter line.…”
Section: Pancreatic Ductal Epithelial Cells Are Incompetent To Transdmentioning
confidence: 59%
“…The outer layer or tunica adventitia is populated by adventitial fibroblasts, is rich in collagen, does not contain elastic fibers, and is separated by the tunica media by the external elastic lamina (reviewed in Wagenseil and Mecham 2009). Some studies have suggested that the adventitial layer contains progenitors that trans-differentiate into VSMCs (Sartore et al 2001;Hoofnagle et al 2004;Hu et al 2004;Passman et al 2008). The composition of the ECM secreted by vascular cell types, and by VSMCs in particular, varies depending on the type of blood vessel and in response to developmental, physiological, and pathological stimuli (Kelleher et al 2004;Xu and Shi 2014).…”
Section: Structure Of the Arterial Vessel Wallmentioning
confidence: 99%
“…(6) The Sca1 expression mentioned earlier in the adventitia has been independently confirmed in mouse aorta and mesenteric and femoral arteries. (25) More importantly, Sca1 + cells immune-selected from the aortic adventitia were found capable of smooth muscle and endothelial differentiation. Moreover, when the Sca1-selected cells were treated with Bone Morphogenetic Protein 2 (BMP2), colonies formed that stained positive by alizarin red, suggesting osteogenic differentiation.…”
Section: Cd31mentioning
confidence: 99%
“…(18,19) Multiple studies have demonstrated that vascular mesenchymal cells, including microvascular pericytes, so-called calcifying vascular cells and SMCs, undergo osteochondrogenic lineage differentiation spontaneously or under special conditions such as hyperphosphatemia. (18,20) In recent times, these traditional views of vascular biology have been revised by the discovery of immature stem/progenitor cell populations, relevant to endothelial (21,22), smooth muscle (23)(24)(25), myeloid (26) and multipotent mesenchymal lineage (27) that have been shown to participate in postnatal vasculogenesis and vascular wall remodeling. An increasing body of evidence points to the existence of these different progenitor cell types within embryonic, fetal and adult vessel walls, where they may reside either constitutively or appear as a result of circulating migration.…”
Section: Isi: Ketertarikan Para Ilmuwan Akan Vascular Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation